FORAGE POTENTIAL AND ADAPTATION OF Alysicarpus vaginalis IN BALI PROVINCE - Suarna, I Wayan; Suryani, Ni Nyoman; Budiasa, K.M (Pastura; Vol 8 No 1 (2018): Pastura Vol. 8 No. 1 Tahun 2018DO - 10.24843/Pastura.2018.v08.i01.p03, 2019)
Climate change that has hit the world requires to make adaptation efforts so that agricultural productivity can be maintained. Alysicarpus vaginalis is one of the local variety forage that can grow in a various of environmental conditions. In this regard, a survey research has been carried out to study various types of local forages throughout Bali. The aim of the research is to obtain forages that have superior properties and can be developed in various regions in Bali. The survey sampling location refers to a map prepared specifically for that by overlaying a map of soil types, land use maps, and climate maps. Based on the results of the survey, several species of local forages that have superior characteristics have been found. One of them is Alysicarpus vaginalis plant as a forage superior, Alysicarpus vaginalis forage production as much as 46,302 kg DM ha-1 with 0.21% botanical composition. Keywords: Alysicarpus vaginalis, superior legumes, tropical forage